Central Government’s Roles in New Autonomous Region Development in Bandung Barat - Setiawan, Irawan (UI Scholars Hub, 2012)
This research discusses the effectiveness of placing Ngamprah sub-district as the capital city of Bandung Barat District, using qualitative approach and central place theory which covers the center of administration and center of growth dimensions. The conclusion is that the center of administration and the center of growth dimensions analysis have not shown the effectiveness of Ngamprah sub-district as the Capital City of Bandung Barat District. Our recommendation is for the local government to construct railroads to tie other sub-districts to Ngamprah, i. e. the roads linking Cisarua and Ngamprah, both from Jambudipa and Cipada, to establish Ngamprah Market to potentially become the District’s business center, and to build up housing area.